Coloured hybrid materials: exploiting an emergent surface property of fluorinated Al2O3 containing anthocyanins and betacyanins. Issue 32 (29th July 2022) - Pérez-Ramírez, Erik; Torres, Ivan Kaleb; Martínez-Ortiz, Ma. Jesús; Rivera, José L.; Felipe, Carlos; Guzmán, Ariel; Ibarra, Ilich A.; Lima, Enrique
Abstract : Not just simple colours: inorganic matrixes were evaluated to characterize aluminium and fluorine species ([AlO4 5− ], [AlO5 7− ], [AlO6 9− ], [AlF4 − ], [AlF5 2− ] and [AlF6 3− ]) by PXRD, XPS, 27 Al MAS-NMR and IR-ATR. Abstract : Two fluorinated γ-Al2 O3 series were synthesized by a sol–gel method with two solvents (2-propanol and 2-butanol), two aluminium sources (ATB and ATP) and one fluorine source (Na3 AlF6 ). The resulting inorganic matrixes were evaluated to characterize aluminium and fluorine species ([AlO4 5− ], [AlO5 7− ], [AlO6 9− ], [AlF4 − ], [AlF5 2− ] and [AlF6 3− ]) by powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), 27 Al magic angle spinning nuclear magnetic resonance ( 27 Al MAS-NMR) and infrared spectroscopy (IR-ATR). BET and BJH analyses using the nitrogen isotherms of these materials allowed identifying a clear trend in some textural parameters such as specific surface area and fluorine content. These results were confirmed by scanning electron microscopy (SEM). Chemical affinity and acid surface properties were evidenced with colour shifts in two groups of hybrid pigments, prepared with natural anthocyanins ( Brassica oleracea ) and betacyanins ( Bougainvillea glabra ).